Management of Infected Nonunion of Long Bones, A Case Series (Journal of Pakistan Orthopaedic Association, 2018)
Objective: To evaluate the management of long bones infected nonunion.Methods: This retrospective study was conducted between July 2014 and July 2017.  Inclusion criteria was to include all cases of infected nonunion of long bones with no evidence of union within six to eight months, irrespective of loss of bone. All patients were thoroughly investigated and evaluated clinically, labs and X-rays. All patients were assessed by the Association for the Study and Application of Methods of Ilizarov(ASAMI) criteria for radiological and functional outcomes.Results: In this study, Twenty cases of infected nonunion (tibia 14, and femur 6) were used. There were 14 males and 6 female subjects, for whom the average age was 35±6.21 SD (range 18-52). 15 patients had open fracture while 5 patients were post internal fixation. Infection was eradicated and the union was achieved in all cases. The average time to union was a mean of 10±1.1SD months, ranging from 8 to 12 months). The follow up was a mean of 18 months (range 16-20 months). In case of tibia and femur as per the ASAMI score, radiological results were excellent in 14/20 (70%) and good in 4/20 (20 %), 2/20 (10%) showed fair results and no patient had poor result. Functional outcomes were excellent in 13/20 (65%) subjects, 5/17 (25%) were rated as good, and 2/20 (10%) as fair. Union was achieved in all three cases of humerus.Conclusion: Infected non-unions pose challenge to both patient and surgeon. Ilizarov fixator gave good and excellent results in complex non-union of long bones by eradicating infection, filling the defect with bone transport and correcting the deformity.